Management Style of Tourism Business Operators Changed During Covid-19 in Luang Prabang Capital, Luang Prabang Province - ONEKEO, Sengla; LAMPHET, Thieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Tourism is one of the fastest growing industries in the world; the government of the Lao People's Democratic Republic has determined and announced the implementation of the development and promotion of cultural, natural and historical tourism. Due to the change in global trends and the outbreak of the covid-19 disease, tourism is in danger but the tourism business must continue to make the management style of the tourism business operators suffer from management problems that affect the tourism business both directly and indirectly., This research aims to study the management style of tourism business operators that have changed during Covid-19 in Luang Prabang capital, Luang Prabang province and the management guidelines of tourism business operators during Covid-19, which identified 20 tourism business units in the capital of Prabang, including: tourism company business, tourism source business, hotel businessmen, guest houses, restaurants, souvenir shops , is a qualitative method of study with the tools used in the study, such as: random interviews from tourism business operators regarding the management style of tourism business during Covid-19 in terms of planning, organization, leadership and control, as well as summarizing the management of tourism business operators during Covid-19.